Genetic parameter estimation to milk yield and fat and protein yield deviated from 3% of concentration in milk, in dairy herds of southern Chile - Uribe, Héctor; González, Humberto; Gatica, Carlos (Austral Journal of Veterinary Sciences, 2017)
Chilean milk processing industry is providing clear signs to milk farmers regarding the significant importance of milk solids within raw milk payment schemes. A litre of milk containing 3% of fat and 3% of protein is defined as a basic litre and, each additional kilo of fat and/or protein receives an extra payment. These are new production traits which must be researched on. In this study, 64,029 lactations, on 24 Región de Los Ríos at Southern of Chile herds, were used. Genetic parameters for milk yield and fat and protein above 3% yield were estimated. A multiple trait linear model, solved by BLUP methodology, was used. Variance components were estimated using AIREMLF90 and VCE software. Estimated heritability for milk yield, and fat and protein above 3% yield were 0.16±0.004, 0.44±0.007 and 0.42±0.006, respectively. Estimated genetic correlations were –0.285 and –0.331 between milk yield and fat and protein above 3% yield, respectively. It is concluded that there exist genetic variation for the two new traits proposed by the Chilean milk processing industry and, genetic selection for these traits should be done based on their estimated breeding values. However these two traits, plus milk yield, should be included in a selection index to account for the negative genetic correlations among them and minimise selection against milk yield.